A novel allocation strategy for the difficult‐to‐allocate donor: audit of deceased donor kidneys utilised for preemptive recipients within Western Australia. Issue 2 (23rd February 2023) - Kulkarni, Rishabh; Wong, Zo E.; Downing, Jonathan; Swaminathan, Ramyasuda; Chan, Doris; Chakera, Aron; Abraham, Abu; Irish, Ashley; Lim, Wai; D'Orsogna, Lloyd J.
Abstract: Kidney donor allocation can occasionally be difficult in Australia given a small population spread over vast distances. Therefore, between 2017 and 2019 our service allowed transplantation from deceased donors into local (same‐state) preemptive recipients, only if no well‐matched dialysis‐dependent transplant waitlist recipient was available. Transplantation using this novel allocation pathway was associated with good clinical and immunological outcomes.